La magistrature française et la culture de guerre. Le cas Malicet - Annie Deperchin (Clio@Themis)
At the eve of the WW1, French jurists believed they were the most qualified persons, regarding their professional activities, to protect law and justice. Moreover, judges used their skills to fight, as they were combatants of the home front, German and Autro-Hungarian people who lived in France, often for a long time before the war, even though they were not personally involved into war. Despite the spirit and principles of law, french courts confiscated enemies’ properties and forbade Germans and Austro-Hungarian’ claims. Doing so, they praticised a sort of judicial warfare which could be explained by the violence of their patriotic feelings. It seemed impossible to think a different way and certainly too difficult to brave the public opinion which was intrumentalized by nationalist press. So the major part of the judges preferred to keep silent rather than maintain the pacific culture of law. Pierre Malicet, a judge from the occupied territories, wrote his diary throuht out the war. He refused absolutely to be submerged by war culture and especially hate. As Wilson did (he shared many points of view with the american president) he believed that war itself constituted the supreme evil and it would be unmoral such as unfair to get any advantage as a consequence of the victory. Malicet’s case might be singular, nevertheless it shows that it would be wrong to assess that all the french judges and magistrates were submerged by war culture.